Sorghum-peanut intercropping under salt stress mediates rhizosphere microbial community shaping in sorghum by affecting soil sugar metabolism pathways - Shao, Xia; Yang, Chunmei; Chen, Yuxuan; Liu, Chang; Liu, Chunjuan; Shi, Xiaolong; Zhou, Yufei (Frontiers in Microbiology, 2025)
Soil salinization is a substantial impediment to agricultural production, and investigating sustainable mitigation measures is essential for addressing food security. We conducted a two-year pot experiment to investigate the shaping mechanism of sorghum rhizosphere microbial community in sorghum-peanut intercropping system under salt stress. The experiment comprised four treatments: sole-cropped sorghum under normal soil conditions (NSS), intercropped sorghum under normal soil conditions (NIS), sole-cropped sorghum under salt-stress conditions (SSS), and intercropped sorghum under salt-stress conditions (SIS). The sorghum rhizosphere soil metabolites were examined using GC–MS, and the rhizosphere microbial community was characterized through metabolome sequencing. We identified 123 metabolites across treatments, with significant differences between normal and salt-stress soil conditions. The major metabolite classes included carbohydrates, alcohols, and acids. Key carbohydrates, including fructose and sucrose, were significantly reduced in the SIS than in SSS, NSS, and NIS treatments. Metabolic pathway analyses revealed that these differences were primarily associated with “Fructose and mannose metabolism,” “Starch and sucrose metabolism” and “ABC transporter.” Metabolome analyses revealed significant differences in microbial community structure across diverse soil conditions and cropping patterns. At phylum level, Proteobacteria, Gemmatimonadetes, and Verrucomicrobia predominated, with their relative abundance experiencing substantial changes under salt stress. SIS facilitated the enrichment of specific genera (Rhodanobacter), which were associated with soil health and stress tolerance. Additionally, the responses of rare microbial taxa to salt stress and intercropping varied, with specific rare microbial taxa (Rhizopus) exhibiting relative abundance under salt stress. Correlation analysis of metabolites and microbial taxa revealed that certain carbohydrates were significantly positively correlated with specific microbial phyla (Cyanobacteria and Nitrospirae) while demonstrating a significant negative correlation with Planctomycetota and Bacteroidota. These correlations indicate that sorghum intercropped with peanuts can promote the enrichment of microbial taxa under salt stress, thereby enhancing soil metabolic functions and stress tolerance by optimizing the rhizosphere microbial community. This study reveals the mechanism through which sorghum-peanut intercropping under salt stress influences the composition of sorghum’s rhizosphere microbial community by modulating soil sugar metabolism pathways. This finding provides a new perspective on sustainable agricultural practices in saline soils and emphasizes the pivotal role of plant-metabolite-microbe interactions in abiotic stress mitigation.